Improvisation for Agricultural Communicators: Investigating the Effect of Paired Role-Play Discussions On Students’ Empathy Development Using a Quasi-Experiment - Jean A Parrella; Carrie N Baker; Holli Leggette; Deb W Dunsford (Journal of Applied Communications, 2022)
Empathy is integral to effective civil discourse because it enables people to understand others’ perspectives (cognitive) and feel concern toward others’ feelings (affective). Although no studies have empirically investigated agricultural communications students’ empathy development, scholars in other disciplines have identified improvisational role-play exercises as effective means to develop students’ empathy skills. Therefore, we sought to determine how paired role-play discussions affected agricultural communications students’ empathy development when compared to class-wide discussions during the course of one semester using a quasi-experimental pretest-posttest control group research design. The pretest-posttest survey instrument included Reniers et al.’s (2011) Questionnaire of Cognitive and Affective Empathy. Using Kolb’s (1981) experiential learning cycle as a guide, we developed study materials (i.e., lectures, case studies, readings, discussion exercises) focused on relevant skills needed to meet industry demands (i.e., brand assimilation, consumer engagement, public relations, content marketing) and implemented the materials during four class periods. We only facilitated active experimentation through role-play with students in the treatment group. After analyzing the data from 53 usable pretest-posttest responses using a mixed design repeated measures ANOVA, we found that paired role-play discussions and class-wide discussions, both focused on recognizing and affirming opposing perspectives, statistically significantly improved students’ cognitive empathy and total empathy, but not affective empathy. Therefore, we recommend instructors facilitate the type of discussion that would suit their teaching style, classroom dynamic, and students’ learning style best. If an improvement in affective empathy is also desired, then adapting the materials to include a focus on emotion contagion is necessary.
Keywords: affective empathy; agricultural communications; cognitive empathy; mixed design; quasi-experiment